Group Counseling Using Aversion Conditioning Techniques to Reduce Aggressive Behavior Of Class VIII Students Of MTS Darul Huffaz - Murni, Sri; Fitri, Gita; Ismaniar, Ismaniar (Universitas Negeri Padang, 2024)
This research aims to analyze the reduction of aggressive behavior through group counseling using aversion conditioning techniques in class VIII students at MTs Darul Huffaz. This research used the guidance and counseling action research (PTBK) method with subjects of 10 students selected using purposive sampling. The results of the research showed that in the actions from cycle I to cycle II there was a decrease in students' aggressive behavior. Group counseling service activities in reducing the aggressive behavior of class VIII students at MTs Darul Huffaz had been carried out well. This is proven by the results of the achievement of cycle II results which show a decrease in students' aggressive behavior, namely by 8 students or equal to 80% and these results have achieved the target set by researchers, namely 6 students. Results of the student aggressive behavior questionnaire instrument with group counseling services This research shows that starting from the activities before the action until the research ended, the results were quite satisfactory because there was a decrease in each cycle, namely in cycle I after the service was provided, the average score obtained by students only decreased for 3 students, while students who still experienced behavior aggressive is the same as 7 students. And after the service was carried out in cycle II, the average score obtained by students decreased in aggressive behavior by 8 students, while the students who still experienced aggressive behavior in the moderate category were the same as 2 students and had reached the expected target. Keywords: Group Counseling, Aversion, Aggressive Behavior